Industrial waste treatment handbook. - Woodard, Frank, 1939- (Boston : Butterworth-Heinemann, 2001)
Samenvatting:All industries produce waste products that unless treated or mitigated insome way will be harmful to the human or natural environment. These wasteproducts will generally need to be identified according to the industrialprocess in question, neutralized or rendered less harmful and finallydisposed of into the surrounding land, air or watercourses. It istherefore of vital importance to every environmental, pollution or plantmanager or engineer that these processes be fully understood andimplemented or the cost to either the company or the environment can becatastrophic.With increasing government regulation of pollution, as well aswillingness to levy punitive fines for transgressions, and theever-present financial imperative to carry out these activities in themost efficient and cost-effective manner it is the responsibility of theprofessionals in question to ensure that they have the most up-to-dateinformation available at their disposal. This book provides not onlythat, but the only available methodology for identifying which wastetypes are produced from which industrial processes, and how they can betreated. This unique feature makes this book one that everyenvironmental, industrial and plant manager, engineer and consultant willwant to have on their bookshelf.Essential aspect of, and requirement for, all manufacturing industryThe only up-to-date book on this subject area availableTakes a practical applications standpoint, not a theoretical approach
Keywords: Afvalstoffenmanagement; Vuilverwerking